The Tales from Lost Chronicles: Reconstructing History of Partition in Selected Pakistani Fiction - Sadaf Mehmood (JSSH, 2023)
Postmodernist evolution theorizes fluctuating homogeneity of meta- narratives by stabilizing heterogeneity of mini-narratives. Partition of Sub- continent has produced national histories to count the demographic details of the tragic event. New historicists challenge the authenticity of historical narratives through subjective representation. The present study explores how partition event represented in meta-narratives, is reconstructed in mini- narratives. To investigate this, Bapsi Sidhwa’s Ice Candy Man is selected as partition fiction. The study is significant to observe that novels on the event of India Pakistan partition have biased possibilities, thus, different perspectives of the event provide multiple yet distinct perspectives of the event from the writer’s side opinion. The study aims to show how selected fiction depicts religion, altered history, and politics through shared symbols of coexistence in the subcontinent. There is a gap in the exploration of Indo- Pak novels as a means of displaying integration of shared existence. In the light of New Historicism, I examine the gaps that are present in the Ice Candy Man. From vantage point, this study provides an alternative lens to perceive the uncertainties, and insecurities of unidentified people who experienced the turmoil of partition and remained invisible in the historical documentation. In so doing the study gauges the silence of history in representation of the sacrifices of minorities. The selected fiction is significant to highlight the untold and unknown heroic contribution of Parsee community in the tragic event of Partition.